Electroacupuncture Ameliorates Acute Myocardial Ischemia: A Potential Role of the Locus Coeruleus. (31st March 2020) - Wu, Xin; Wang, Kun; Cui, Shuai; Wu, Shengbing; Zhu, Guoqi; Zhou, Meiqi
Abstract : The locus coeruleus (LC) is closely linked with cardiovascular disease. However, whether it mediates the alleviating effect of electroacupuncture (EA) on acute myocardial ischemia (AMI) remains unclear. A rat model of myocardial ischemia was established through occlusion of the left anterior descending coronary artery. Multichannel in vivo recording and other techniques were used to assess neurons in the LC, norepinephrine (NE) and dopamine (DA) levels in central and myocardial tissue, serum levels of inflammatory factors, and cardiac function. After induction of AMI, LC neuron activity increased and the central NE concentrations increased, while those of DA decreased. Moreover, the serum levels of high-sensitivity C-reactive protein (hs-CRP) increased, whereas those of interleukin-10 (IL-10) decreased. However, these effects were reversed by EA. Additionally, LC lesioning affected NE and DA levels in myocardial tissue and weakened the antimyocardial ischemic effect of EA. Collectively, our results indicated that LC is closely related to AMI and plays an important role in the antimyocardial ischemic effect of EA. This mechanism may be related to inhibition of LC neuron activity by EA, which inhibits the release of large amounts of hs-CRP and promotes that of IL-10 in the serum. Besides, after LC lesioning, EA may improve cardiac function by inhibiting the release of large amounts of NE and promoting the release of DA in myocardial tissue.